If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying n + -3 = -4n + -1(n + -3) Reorder the terms: -3 + n = -4n + -1(n + -3) Reorder the terms: -3 + n = -4n + -1(-3 + n) -3 + n = -4n + (-3 * -1 + n * -1) -3 + n = -4n + (3 + -1n) Reorder the terms: -3 + n = 3 + -4n + -1n Combine like terms: -4n + -1n = -5n -3 + n = 3 + -5n Solving -3 + n = 3 + -5n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '5n' to each side of the equation. -3 + n + 5n = 3 + -5n + 5n Combine like terms: n + 5n = 6n -3 + 6n = 3 + -5n + 5n Combine like terms: -5n + 5n = 0 -3 + 6n = 3 + 0 -3 + 6n = 3 Add '3' to each side of the equation. -3 + 3 + 6n = 3 + 3 Combine like terms: -3 + 3 = 0 0 + 6n = 3 + 3 6n = 3 + 3 Combine like terms: 3 + 3 = 6 6n = 6 Divide each side by '6'. n = 1 Simplifying n = 1
| 2y-3y+-1=4 | | -7(3r-4)=-20+9r | | 28-13.8x=-54.8 | | 4s-12*(s-2)=s | | 20z+3z-21z-1=13 | | -78=6U+12 | | 3x-3+x-3=90 | | (6x^3y^2)(-2x^2y)= | | -6+3(1-8k)=27 | | -22=2-3r+7r | | 5(3x-6)=10 | | -0.5s=-28 | | 198=g+12 | | 42=-2(v-8) | | 7+0=x | | -21=9d-7d | | 220=g+70 | | 5(c-6)c+11=24 | | -12=6(x+7) | | 7+y+12y=7 | | -8n+2=-3n-3 | | -5p-24=21(-1+3p) | | b+3-9=29 | | 4(-3+v)=36 | | f(5)=4x-3 | | -5(2s+2m)= | | -111=-3(1+6n) | | 50+5x=15+12x | | 12x-5=4x-1 | | 7x+11=7+7x | | -2(-4+y)-5y=15 | | -13+4b=-3b-7 |